Who Denigrates Today’s Youth?: The Role of Age, Implicit Theories, and Sharing the Same Negative Trait - Protzko, John; Schooler, Jonathan W. (Frontiers in Psychology, 2022)
Adults perceive the youth of the present as being worse than from when they were young. This phenomenon has been shown to be a product of a memory bias, adults are unable to accurately recall what children were like in the past so they impose their current selves onto their memories. In two studies using American adults (N = 2,764), we seek to connect this finding to age, implicit theories of change, and extend the beliefs in the decline of the youth to new domains. Here we show as people age, they hold harsher beliefs about present children. Those who believe a trait does not change throughout the lifespan exhibit more forgiving attitudes towards the youth of today, believing they may not be in such decline on that trait. Finally, people who are low in a negative trait believe strongly that children are becoming more deficient in that particular trait (e.g., those who are not narcissistic believe the youth are becoming more narcissistic).